(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
This contribution briefly examines the survey strategies of the University of Milan for the study of the site of Populonia, in the area of Centro Velico, Baratti bay. This area is uneven, with steep changes in the elevation, partly exposed to strong marine erosion and partly covered with vegetation. A structure for extraction of salt attests an inhabitation of the place already in Bronze Age; after a phase of abandonment, this area became a cemetery, which was in use at least until Imperial Age.